Pendekatan Filsafat Islam al-Ghazali dalam Pembinaan Akhlak Mulia Siswa SD Negeri 03 Karang (Studi Analisis Aksiologi dalam Filsafat Islam) - Mujiburrohman, Mujiburrohman; Prasetyo, Dony Agus (TSAQOFAH, 2026)
Although the cultivation of noble character in elementary schools is often cited as a key educational goal, the systematic application of Islamic philosophical approaches, particularly al-Ghazali’s thought in the context of public schools has rarely been examined from an axiological perspective. This case study aims to analyze the implementation of al-Ghazali’s Islamic philosophical approach in fostering students’ noble character at SD Negeri 03 Karang, with an emphasis on the axiology of Islamic education, namely how moral values and goals are actualized in educational practice. The research employs a qualitative approach with a case study design, drawing on data obtained through in-depth interviews with four teachers and observations of the school environment and activities. The findings show that the integration of spiritual and Sufi-based values inspired by al-Ghazali, such as the emphasis on character (akhlak) as the core of education, strengthens students’ character formation through the habituation of value-laden behaviors, the reinforcement of religious consciousness, and the cultivation of moral responsibility. However, the implementation of this approach faces challenges, including the dominance of a more secular-oriented curriculum and limited formal space for the explicit internalization of Islamic values. This study contributes to enriching the discourse on the axiology of Islam in modern education by demonstrating the practical relevance of al-Ghazali’s ideas for character education in public elementary schools, while also indicating the need for stronger institutional support to ensure more consistent and sustainable integration of Islamic values.